Activity Test of Taro Leaf Extract Gel (Colocasia esculenta [L]) as an Accelerated Healing of Type II Burns in Rabbits (Oryctolagus cuniculus) With HPMC Base - Afandi, Ferian (Jurnal Mahasiswa Kesehatan, 2022)
Taro leaves have activity as an acceleration of burn healing and contain secondary metabolites of flavonoids, saponins, tannins and steroids which are known to help accelerate the healing of burns. The gel preparation was chosen because it consists of small inorganic particles or very large inorganic atoms, which are penetrated by the liquid. The gel has a more pronounced water content compared to other semi-solid arrangements. Once the water content is gone after use, it will give a cool sensation to the skin. In this study, a gel formulation was carried out with 3 variations in the concentration of taro leaf extract of 5%, 10% and 20%. The preparations were then subjected to physical evaluation consisting of organoleptic tests, homogeneity, pH analysis, viscosity, adhesion and spreadability. Based on the test results, it was found that formula III is the most optimal formula. Burns testing on 5 rabbits that had been injured found the percentage of burn healing, formula 1 was 54%, formula II was 62% and formula III was 69%. The results of statistical analysis showed that the data were homogeneously distributed (p = > 0.05) and the data were normally distributed (p = > 0.05).Keywords: Burns, taro leaf extract, Colocasia escluenta L, Rabbit, Octolygus cuniculus